Multifunctional Bangka kaolin for zeolite 3A pellet synthesis and its application in ethanol dehydration - Maria Ulfah; Pasymi Pasymi; Amelia Amir; Ulung Muhammad Sutopo; Burmawi Burmawi; Melia Laniwati Gunawan; I.G.B.N. Makertihartha (Center of Biomass & Renewable Energy (CBIORE), 2026)
The development of cost-effective, highly efficient adsorbents for bioethanol dehydration is crucial to advancing sustainable biofuel integration, including the upcoming E10 fuel-blending mandates in Indonesia. This study evaluates the multifunctional capability of locally sourced Bangka kaolin as both a structural precursor and an active binder for the synthesis of binder-converted Zeolite 3A pellets, specifically tailored for ethanol-water azeotrope separation. The fabrication procedure followed a comprehensive two-stage method, commencing with the thermal calcination of raw kaolin at 600°C and 750°C to generate reactive metakaolin. Subsequently, a hydrothermal synthesis strategy was employed using different alkalinity settings, governed by H2O/Na2O molar ratios of 40, 43, and 45, corresponding to NaOH concentrations of 2.88 M, 2.67 M, and 2.55 M, respectively. This solution-gel matrix was homogenized with synthesized Zeolite Na-A powder, extruded into pellets, and subjected to an in-situ hydrothermal crystallization phase to transform the amorphous binder into a crystalline Zeolite A framework. Final structural modification was performed via successive liquid-phase potassium-ion exchanges using 21 wt.% and 11 wt.% chloride potassium solutions to shrink the effective pore opening to approximately 3A. Structural and compositional assessments via X-ray diffraction (XRD) and X-ray fluorescence (XRF) confirmed the successful formation of Zeolite A frameworks with no residual sodium oxide (0.00% Na2O), achieving significant potassium loading (30.15–34.58 wt.% K2O) and moderate relative crystallinities ranging from 55% to 74%. Textural diagnostics from N2 physisorption demonstrated that the synthesized pellets exhibit an IUPAC Type IV isotherm coupled with a Type H3 hysteresis loop, indicating a hierarchically organized pore structure with crucial secondary mesopores. Performance evaluation during dynamic ethanol-water separation confirmed that the synthesized Zeolite 3A pellets exhibit an enhanced water adsorption capacity of up to 27.97 wt.% for the ZKA-750-45 sample, yielding fuel-grade bioethanol with a peak purity of 99.7 wt.%.